مساهمة في تقويم الجريان السطحي في منطقة حوض السن - علي محمد الأسعد; غطفان عبد الكريم عمار; نبيل نديم حسن (Tishreen University, 2019)
المياه السطحية هي المصدر الحيوي لمجموعة من السدود المنفّذة على مجاري الأنهار خارج منطقة حوض السن، الواقعة في القسم المتوسّط من الساحل السوري؛ لذا فإنّ الهدف الرئيس من هذا البحث هو دراسة الجريان السطحي في منطقة البحث وتقويمه، باستخدام برنامجي نظام المعلومات الجغرافي (GIS) والحزمة الإحصائية للعلوم الاجتماعية SPSS. أجريت قياسات فعلية يومية لمدة سنتين، لكلٍّ من الهطل المطري في 16 محطة مناخية، والجريان السطحي في 13 نقطة قياس سطحية، حيث قُدّرت كميّة الجريان السطحي الوسطي السنوي الإجمالية عند مخارج الأحواض الفرعية بـ (31.224 MCM). وبمقارنتها بمتوسط كمّية الهطل المطري السنوي في منطقة الدراسة البالغة (499.36 MCM)، فإنّ قيمة معامل الجريان السطحي تساوي  0.0625؛ أي أنّ الفواقد المائية بالتبخر والتسرّب كبيرة جداً، وهذا ما أكّدته القياسات الحقلية. ومن المهم للغاية هنا اعتماد طرائق الري الحديثة، وتطبيق قانون التشريع المائي، والإدارة المتكاملة للموارد المائية، لتلبية الاحتياجات المستقبلية من المياه. Surface water is the vital source of many dams executed on the river valleys outside Assin Basin, which is situated at the central part of the Syrian Coast. So, the main objective of this paper is to study and evaluate the surface runoff in the research area, using (GIS) and (SPSS) softwares.  Actual daily measurements were carried out for 2 years, to measure rainfall at 16 meteorological station, and surface discharge at 13 surface measurement point. The mean annual runoff flow at the sub-basins outlets was estimated to be (31.224 MCM). Compared with the overall precipitation in the study area (499.36 MCM/year), the surface runoff coefficient is 0.0625. This indicates that water losses by evaporation and infiltration are very big as approved by the field measurements. Of major importance in this context is the adoption of modern irrigation methods, applying water legislation law and an integrated water resources management (IWRM), to meet the future water demands.